Cover Image. (28th April 2020) - Teusink‐Cross, Ashley; Davies, Stella M.; Grimley, Michael S.; Chandra, Sharat; Flannery, Amanda; Dandoy, Christopher E.; Nelson, Adam S.; Marsh, Rebecca A.; Jacoby, Brandon; Lane, Adam; Khandelwal, Pooja
Abstract : The cover image is based on the Original Article Ibrutinib for the treatment of chronic graft‐vs‐host disease in pediatric hematopoietic stem cell transplant patients: A single‐center experience by Ashley Teusink‐Cross et al., https://doi.org/10.1111/petr.13692 .